2023
DOI: 10.3390/microorganisms11030748
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Bacteria with Quorum Sensing and Quenching Activities from Hydrothermal Vents in the Okinawa Trough

Abstract: Quorum sensing (QS) is a chemical communication system by which bacteria coordinate gene expression and social behaviors. Quorum quenching (QQ) refers to processes of inhibiting the QS pathway. Deep-sea hydrothermal vents are extreme marine environments, where abundant and diverse microbial communities live. However, the nature of chemical communication in bacteria inhabiting the hydrothermal vent is poorly understood. In this study, the QS and QQ activities with N-acyl homoserine lactones (AHLs) as the autoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Additionally, metagenomics studies reported that Vibrionales, Pseudomonadales, or Alteromonadales are the main contributors to AHL production [ 32 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Furthermore, it has been demonstrated that Gammaproteobacteria AHL pathways regulate various traits that may have significance in biogeochemical processes, including biofilm regulation, production of hydrolytic enzymes, siderophores, and motility [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, metagenomics studies reported that Vibrionales, Pseudomonadales, or Alteromonadales are the main contributors to AHL production [ 32 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Furthermore, it has been demonstrated that Gammaproteobacteria AHL pathways regulate various traits that may have significance in biogeochemical processes, including biofilm regulation, production of hydrolytic enzymes, siderophores, and motility [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the isolated bacteria were screened for AHL production using a 96-well microtiter plate assay [ 49 , 50 ] with slight modifications. In brief, the reporter strain A136 was grown overnight at 28 °C at 150 rpm in 5 mL LB broth supplemented with 50 μg/mL spectinomycin and 4.5 μg/mL tetracycline, while the test bacteria were grown in 75 μL LB broth in a 96-well microtiter plate.…”
Section: Methodsmentioning
confidence: 99%
“…Although not typically considered a major player in marine ecosystems, Hyphomicrobiales is a metabolically and morphologically heterogeneous group [51]. This group has been documented in studies focused on deep environments, such as hydrothermal vents displaying quorum sensing activities [52], or marine sediments, where it may be involved in organic matter degradation. Genera within Hyphomicrobiales include aerobic chemoheterotrophs and facultatively methylotrophs, whereas some can grow anaerobically by denitri cation or fermentation [53].…”
Section: Non-cyanobacterial Diazotrophsmentioning
confidence: 99%